Cities on the Edge, Cities of Enchantment: Invisible Cities in the Far North - Egeler Matthias; Jónsdóttir Dagrún Ósk (Miscellanea Geographica: Regional Studies on Development)
Calvino’s Invisible Cities tells a multitude of stories of invisible, unreal, utopian and anti-utopian cities and explores ‘the hidden reasons which bring men to live in cities: reasons which remain valid over and above any crisis’. Our contribution takes up some of the themes that Calvino places at the heart of his poetic meditation on city life. This includes his praise of magical enchantment; the desire for human company that pervades his meditations on the desert traveller’s – the solitary individual’s – view of the city; and the fundamental role of the human action that is most central to Calvino’s book, namely, storytelling itself. To pursue these themes, we take the reader on a journey to some of the northernmost inhabited parts of Iceland, where habitation itself is crumbling.